The prognostic value of TP53 mutations in hypopharyngeal squamous cell carcinoma - Omura, Go (BMC Cancer, 2017)
BACKGROUND: TP53 is the most frequently mutated gene in human cancers. Previous studies reported that TP53 mutations correlated with poor prognoses in patients with head and neck squamous cell carcinoma (HNSCC). However, the relationship between TP53 mutations and hypopharyngeal squamous cell carcinoma (HPSCC) is not known. The current study aimed to evaluate TP53 mutation status as a predictive biomarker in patients with HPSCC. METHODS: We retrospectively reviewed the clinical charts of 57 HPSCC patients treated with initial surgery between 2008 and 2014. TP53 mutation status was determined by Sanger sequencing, and patients were classified into wild-type, missense mutation, and truncating mutation groups. Additionally, p53 expression was determined using immunohistochemistry in surgical specimens. RESULTS: TP53 mutations were identified in 39 (68%) patients. The 3-year disease-specific survival (DSS) rate of wild-type, missense mutation, and truncating mutation group were 94%, 61%, and 43%, respectively. The TP53 mutation group displayed significantly worse DSS and overall survival rates than the wild-type group (P = 0.01 and P = 0.007, respectively). Multivariate analyses revealed that the presence of TP53 mutations and ≥4 metastatic lymph nodes were independent adverse prognostic factors for HPSCC. p53 immunopositivity was detected in 22 patients, including 5 (28%) and 17 (71%) patients in the wild-type and missense mutation groups, whereas none of the patients with truncating mutation exhibited p53 immunopositivity (P = 0.0001). CONCLUSION: The TP53 mutation status correlated with poor prognosis in surgically treated HPSCC patients. Specifically, truncating mutations which were not detected by p53 immunohistochemistry were predictive of worst survival.